A review of product safety regulations in the European Union - Ruohonen Jukka (Springer Vieweg, 2025)
Despite the long and relatively stable historical lineage of product safety regulations, new technologies, changes in the world economy, and other major transformations have in recent years again brought product safety to the forefront of policy debates. As reforms are also underway, there is a motivation to review the complex safety policy framework in the European Union (EU). Thus, building on deliberative policy analysis and an interpretative literature review, this paper reviews the safety policy for nonfood consumer products in the EU. The review covers the historical background and the main laws, administration and enforcement, standardization and harmonization, laws enacted for specific products, notifications delivered by national safety authorities, recalls of dangerous products, and the liability of these. Based on the review and analysis of these themes and the associated literature, some current policy challenges are further discussed.